2012
DOI: 10.6088/ijes.00202030017
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Quality Studies on Cuddalore

Abstract: During the summer of 2009, concentrations of oxides of nitrogen (NO x), oxides of sulphur (So x), suspended particulate matter (SPM) and carbon monoxide (CO) were collected over successive periods of about 8 hour at eight sites. High volume air sampler was used to measure the concentration of Oxides of nitrogen (NO x), Oxides of sulphur (So x), suspended particulate matter (SPM) and battery operated portable CO monitor was used to measure the concentration of carbon monoxide (CO).The results reported pertain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…Air pollution harms every living being, more so the human population and in particular target severely the occupational groups like car drivers, traffic police personnel, parking lot attendants, tunnel workers, road side vendors, owners and employees of uncovered or frequently open commercial establishments in traffic dense and narrow locations, and all users of public places like bus stands, workshops and cinema theaters. The ill effects on health are severe with the fetus, children, and elders and cardiovascular and angina pectoris patients [1] .Also it affects the functioning of heart and brain. At high concentration the impact is fatal.…”
Section: Hazards Due To Various Gases Presentmentioning
confidence: 99%
“…Air pollution harms every living being, more so the human population and in particular target severely the occupational groups like car drivers, traffic police personnel, parking lot attendants, tunnel workers, road side vendors, owners and employees of uncovered or frequently open commercial establishments in traffic dense and narrow locations, and all users of public places like bus stands, workshops and cinema theaters. The ill effects on health are severe with the fetus, children, and elders and cardiovascular and angina pectoris patients [1] .Also it affects the functioning of heart and brain. At high concentration the impact is fatal.…”
Section: Hazards Due To Various Gases Presentmentioning
confidence: 99%
“…Delhi (Prakash et al, 2010), Choudwar, Cuttack district (Bhuyan et al, 2010), Rohtak city (Shukla et al, 2010), Jaipur city (Kumar et al, 2011, Sharma andSharma, 2016), Garhwal (New Tehri), Kumaon (Muktheshwar) (Meena. et al, 2012), Puducherry ( Balashanmugam et al, 2012) 2008). These studies on air pollution in large cities of India concluded that ambient air pollution concentrations are at such levels where serious health effects are possible.…”
Section: Introductionmentioning
confidence: 97%
“…Higher concentration of oxides of sulfur causes bronchitis and also cause acid rain, sulfurous smog, and reduced atmosphere visibility. A combination of particulate matter with sulfur oxides is more harmful than either of them separately (Balashanmugam et al, 2012). Ozone is produced in the upper atmosphere by solar reaction.…”
Section: Introductionmentioning
confidence: 99%